Communication network analysis among Bt corn growers in Isabela, Philippines: A basis for improved agricultural delivery system - Valdez, M. H.; Delos Trinos, C. H. (International Journal of Agricultural Technology, 2021)
The communication network was analyzed by evaluating the usefulness of information, frequency of consultations, and strength of information exchange among the actors in the Bt corn production in the province of Isabela, Philippines. Majority of the respondents were male which aged 48 years old, mostly high school graduates and had been experienced in corn farming for an average of 21 years. Most of them owned an average of 1.60 ha farmland. Corn yield ranged from 50 to 100 cavans producing a net income of Php 38, 130.41. Among the technical information on seed variety, land preparation, weather forecast, and harvesting techniques were rated to be very useful while in the economic information only current market prices and future market prices had been rated to be very useful. These results were common from the three information sources. Frequency of consultation with personal information sources recorded the highest mean value of 5.10 indicating a two to three times a month information exchange. Public information sources obtained an average mean of 2.84 which means four or five times a year contact. It signified a gap between the corn growers and public information sources. Among the mass media only radio is widely used (4.56) at two to three times a month. Personal information sources obtained the highest mean information score of 256.33 exhibiting a strong information exchange with the Bt corn growers. It indicated that the personal information sources mainly composed the communication network of the Bt corn growers in Isabela. Total information scores of public and mass media information sources were low which means information exchange was weak. Only total information score of friends and cellphone revealed significantly related with corn yield. It indicated that information exchange with friends and using cellphone made a great impact on the yield of corn